Major reduction of ultrasound-detected synovitis during subcutaneous tocilizumab treatment: results from a multicentre 24 week study of patients with rheumatoid arthritis. (4th July 2021) - Hammer, HB; Hansen, IMJ; Järvinen, P; Leirisalo-Repo, M; Ziegelasch, M; Agular, B; Terslev, L
Abstract : Objective : Few studies have investigated the efficacy of subcutaneous tocilizumab (TCZ-SC) on ultrasound-detected inflammation. This study aimed to explore the clinical efficacy of TCZ-SC treatment in rheumatoid arthritis (RA) patients and to evaluate the response by ultrasound compared to Composite Disease Activity Scores (CDAS). Method : This open-label, single-arm study enrolled RA patients with inadequate response to conventional synthetic disease-modifying anti-rheumatic drugs initiating TCZ-SC 162 mg once weekly for 24 weeks, with clinical assessments at baseline, 2, 4, 8, 12, 16, 20, and 24 weeks. Ultrasound examinations [semi-quantitative score (0–3) of 36 joints and four tendons] were performed at baseline, 4, 12, and 24 weeks. CDAS and American College of Rheumatology/European League Against Rheumatism (ACR/EULAR) response, and sum scores of ultrasound grey scale/Doppler were calculated. Changes during follow-up were explored by the Mann–Whitney test and correlations by Spearman's rho. Results : In total, 133 patients (mean ± sd age 55.9 ± 12.0 years) were assessed clinically and 110 patients were also examined with ultrasound. All clinical and ultrasound scores decreased significantly after 4 weeks (p < 0.001). At 24 weeks there was EULAR good response in 87.7% and ACR 70% response in 47.4%. Ultrasound scores had no or low correlations with patient-reported outcomes. At 24 weeks, CDAS remission was achieved in 27.4–83.5% and a sum score Doppler of 0 was found in 53.3%. Conclusions : Clinical and ultrasound scores decreased rapidly. Ultrasound scores were not associated with patient-reported variables. Half of the patients reached ultrasound remission, while there were large discrepancies in the percentage of patients reaching remission based on different CDAS. Trial registration: Study ML28691, registered 28 January 2014, ClinicalTrials.gov identifier: NCT02046616